2001
DOI: 10.1016/s0735-1097(01)01333-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of flow velocity reserve by transthoracic Doppler echocardiography and venous adenosine infusion before and after left anterior descending coronary artery stenting

Abstract: Coronary flow reserve, as measured by transthoracic Doppler echocardiography, is impaired in LAD disease; it may identify patients with > or =90% stenosis; and it normalizes early after stenting, even in patients with > or =90% stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
2
4

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(84 citation statements)
references
References 30 publications
2
76
2
4
Order By: Relevance
“…Inter-and intraobserver variabilities in measurements of Doppler velocity in our laboratory were 3.2% and 2%, respectively, 16 whereas intraindividual variability never exceeded (in absolute average values) 2 cm/s, thus providing a maximal Ϯ6% difference in relative terms. 16 Coronary angiography: Cardiac catheterization was performed in all patients by the percutaneous femoral approach. Coronary lumen diameter was measured online with electronic calipers by 2 expert operators performing angiography who were blinded to the Doppler results.…”
Section: Feasibility and Reproducibility Of Cfr Assessmentmentioning
confidence: 67%
See 1 more Smart Citation
“…Inter-and intraobserver variabilities in measurements of Doppler velocity in our laboratory were 3.2% and 2%, respectively, 16 whereas intraindividual variability never exceeded (in absolute average values) 2 cm/s, thus providing a maximal Ϯ6% difference in relative terms. 16 Coronary angiography: Cardiac catheterization was performed in all patients by the percutaneous femoral approach. Coronary lumen diameter was measured online with electronic calipers by 2 expert operators performing angiography who were blinded to the Doppler results.…”
Section: Feasibility and Reproducibility Of Cfr Assessmentmentioning
confidence: 67%
“…Recent advances in color Doppler technology have allowed imaging of the distal LAD 9,10 by transthoracic echocardiography, thereby opening the way to the noninvasive detection of recanalization in acute anterior myocardial infarction, 11 diagnosis of LAD disease by measurement of CFR, [12][13][14][15] and monitoring of changes in CFR after stenting. 16,17 The aim of this study was to assess whether CFR in an angiographically normal LAD is preserved in patients with remote coronary artery disease (CAD), including those with myocardial infarction. CFR was prospectively measured by transthoracic coronary Doppler ultrasound.…”
mentioning
confidence: 99%
“…TDE: TDE was performed as previously described in a modified 2-chamber view, 4,6 using Sequoia C256 and C512 ultrasound systems (Siemens-Acuson, Mountain View, California). The LAD was scanned by a dedicated 7-MHz transducer (3.5 MHz in color Doppler ultrasound) along the anterior interventricular groove, 6 and the PD was scanned using a standard 3.5-MHz transducer (2 MHz in color Doppler ultrasound).…”
Section: Methodsmentioning
confidence: 99%
“…The LAD was scanned by a dedicated 7-MHz transducer (3.5 MHz in color Doppler ultrasound) along the anterior interventricular groove, 6 and the PD was scanned using a standard 3.5-MHz transducer (2 MHz in color Doppler ultrasound). 4 The best long-axis view in color Doppler imaging was obtained to optimize the angle bea Department of Cardiology, "Tor Vergata" University; and b Department of Heart and Great Vessels "A. Reale," "La Sapienza" University, Rome, Italy.…”
Section: Methodsmentioning
confidence: 99%
“…The time required to complete a CFVR test in one artery is around 5-8 minutes depending on the investigators' experience. Pizzuto et al, 2001 revealed CFVR value for the LAD ranging from 2.90±0.58 to 3.050.81 in control group of patients with angiographically normal coronary arteries, and similar values for CFVR were found in <50% LAD in-stent restenosis (Lambertz et al, 1999;. Later, CFVR in angiographically normal LAD patients with remote CAD (presence of previous remote myocardial infarction and wall motion abnormalities) was determined also as preserved (Pizzuto et al, 2004).…”
Section: Cut-off Level For Normal and Pathologic Cfvr 421 Tte Calcumentioning
confidence: 64%